ORIENTASI TEOLOGI FEMINISME RIFFAT HASSAN DALAM KONSEP PENCIPTAAN MANUSIA DI MA’HAD ALI UNIVERSITAS PTIQ JAKARTA - M. Suaib Tahir; Farichah Naily Faizah; Abd. Aziz; Muhammad Zaenal Arifin; Nur Rofiah; Kiki Adnan Muzaki (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This article discusses the thoughts of the Muslim feminist figure, Riffat Hassan, especially regarding his interpretation of the concept of human creation. This article first discusses matters related to feminism in terms of understanding, history, feminism in Islam and the discourse of Riffat Hassan's thoughts. The data source was obtained by the author through observation and literature review from several books, books, journals and verses from the Koran. The results of this research state that according to Riffat Hasan women are not second class creatures created from Adam's bent ribs. On the other hand, men and women are created from the same elements so they have the same essence and existence. Therefore, women have the same potential and position as men